Functions with constant sums over a hyperplane and applications - Kanet Ponpetch; Sukrawan Mavecha; Vichian Laohakosol (My University, 2019)
Two functional equations exhibiting functions with constant sums over points lying in a hyperplane are solved, and the results are applied to characterize major trigonometric and hyperbolic functions.
Keywords: Hyperplane; Constant (computer programming); Functional Equations Stability Results